Arthroscopic reconstruction of anterior cruciate ligament: study of the correlation between failure rate and the procedure technique - А. M. Shormanov; V. Yu. Ulyanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
The failure rate in arthroscopic reconstruction of anterior cruciate ligament (ACL) is conditioned by irrational aligning of the drilled transosseous canals, different mechanical properties of the synthetic or auto/allografts, and the number of fixators. By now the published studies on the correlation between failure rate and methods of arthroscopic ACL reconstruction are few. The objective of this research was the investigation of the correlation between the failure rate and certain techniques of arthroscopic ACL reconstruction in patients with its complete isolated rapture.Materials and methods. The study involved 84 patients who in due time underwent single- or double-bundle reconstruction with synthetic implants, or the reconstruction by a semitendinosus and gracilis autografts. The failure rate was estimated in 3, 6, and 12 months by the presence of true clinical signs of the ACL failure along with the patient’s corresponding complaints of the knee joint instability in regular physical load.Results. No differences were observed in the failures rates after surgeries performed by various arthroscopic reconstruction techniques in all periods of observation revealed by the interpretation of true clinical signs of ACL failure and confirmed by the Fisher's exact test value (р > 0.05) and χ2(р > 0.05) for the three groups overall.Conclusion. The examination of patients with complete isolated ACL rapture in all periods of observation for the three samples revealed no correlation between arthroscopic ACL reconstruction failure rates and the employed techniques.